2017
DOI: 10.1017/s0373463317000078
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Consumption Ratio Analysis for Transiting from Various Ports and Harbours in Asia through the Northern Sea Route

Abstract: The purpose of this study is to determine the navigation efficiency for transiting from various ports in Asia and Rotterdam in Europe via the Northern Sea Route. Navigation efficiency was derived from fuel consumption ratios. Preliminary research results showed that fuel consumption and the amount of carbon dioxide emissions was reduced by transiting from various ports through the European Sea Route, and the navigation efficiencies of the various ports ranked in the following descending order: Yokohama - Busan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…On the other hand, this problem is common to other vehicles where fuel distribution influences stability, such as ships (Chou, Chou, Hsu, & Lu, 2017), where this approach can be extended.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this problem is common to other vehicles where fuel distribution influences stability, such as ships (Chou, Chou, Hsu, & Lu, 2017), where this approach can be extended.…”
Section: Discussionmentioning
confidence: 99%
“…A look at the world map in figure 2 shows the savings in distance that can be achieved with the Arctic routes: for example, a trip between London and Yokohama through the Northwest Passage is 15,700 km and 13,841 km through the Northeast Passage, which is significantly shorter than the route through Suez (21,200 km) or Panama (23,300 km) (Lasserre and Pelletier, 2011). Empirical studies have been conducted to analyse the potential economic impact of Arctic ice melting on shipping routes and these are their findings: (Rahman, Saharuddin and Rasdi ,2014;Stephenson and Smith, 2015;Chou et al, 2017;(Khon, Mokhov and Semenov, 2017)concluded that the opening of the Northern Sea Route as an alternative route for transporting cargoes from the Far East and Europe will affect the maritime sector of Malaysia Economy both positively in agreeing with (Yumashev et al, (2017) and (Melia, Haines and Hawkins, 2017) that the new route may result in a shorter travel distance of up to 40% (Cho, 2012;Hong, 2012;Lu et al, 2014;Mokhov, Khon and Prokof'eva, 2016)between Asia and Europe and negatively (Zhang, Meng and Zhang, 2016)in the scope of 1) political, 2) economy, 3) social, 4) technology 5) environment and 6) legal(Savitzky, 2016)on both developed and emerging economies (Brown, 2015). (Melia, Haines and Hawkins, 2017) suggest that trans-Arctic routes may provide a useful supplement to the traditional canal routes (Faury and Cariou, 2016), but they will likely not replace them (Bensassi et al, 2016)even though (Bekkers, Francois and Rojas-Romagosa, 2017)arguably predict shifts in trade flows (Savitzky, 2016) between Asia and Europe with diversion of trade within Europe(Brown, 2015), heavy shipping traffic in the Arctic and a substantial drop in Suez traffic (Hong, 2012;Mokhov, Khon and Prokof'eva, 2016;Button et al, 2017;Chou et al, 2017)).…”
Section: Economic Impact Of Arctic Ice Melting On Shipping Routesmentioning
confidence: 99%
“…Empirical studies have been conducted to analyse the potential economic impact of Arctic ice melting on shipping routes and these are their findings: (Rahman, Saharuddin and Rasdi ,2014;Stephenson and Smith, 2015;Chou et al, 2017;(Khon, Mokhov and Semenov, 2017)concluded that the opening of the Northern Sea Route as an alternative route for transporting cargoes from the Far East and Europe will affect the maritime sector of Malaysia Economy both positively in agreeing with (Yumashev et al, (2017) and (Melia, Haines and Hawkins, 2017) that the new route may result in a shorter travel distance of up to 40% (Cho, 2012;Hong, 2012;Lu et al, 2014;Mokhov, Khon and Prokof'eva, 2016)between Asia and Europe and negatively (Zhang, Meng and Zhang, 2016)in the scope of 1) political, 2) economy, 3) social, 4) technology 5) environment and 6) legal(Savitzky, 2016)on both developed and emerging economies (Brown, 2015). (Melia, Haines and Hawkins, 2017) suggest that trans-Arctic routes may provide a useful supplement to the traditional canal routes (Faury and Cariou, 2016), but they will likely not replace them (Bensassi et al, 2016)even though (Bekkers, Francois and Rojas-Romagosa, 2017)arguably predict shifts in trade flows (Savitzky, 2016) between Asia and Europe with diversion of trade within Europe(Brown, 2015), heavy shipping traffic in the Arctic and a substantial drop in Suez traffic (Hong, 2012;Mokhov, Khon and Prokof'eva, 2016;Button et al, 2017;Chou et al, 2017)). (Lindstad, Bright and Strømman, 2016) concluded that the results indicate that there are no general climate benefits of utilizing the Northern Sea Route, even with cleaner fuels, since the additional impact of emissions in the Arctic more than off sets the effect of shorter voyages with the biggest economic losses set to occur in Africa (Hong, 2012)and India of CO2 emissions due to global warming (Yumashev et al, 2017;Bekkers, Francois and Rojas-Romagosa, 2017).Countering this argument, (Cho, 2012;Chou et al, 2017) predicts decreased environmental impact due to CO2 emissions.…”
Section: Economic Impact Of Arctic Ice Melting On Shipping Routesmentioning
confidence: 99%
See 2 more Smart Citations